Study of a new fast adaptive filtering algorithm - WANG Zhen-li; ZHANG Xiong-wei; YANG Ji-bin; CHEN Gong (Tongxin xuebao)
A new fast adaptive filtering algorithm was presented by using the correlations between the signal’s former and latter sampling times. The proof of the new algorithm was also presented, which showed that its optimal weight vector was the solution of generalized Wiener equation. The new algorithm was of simple structure, fast convergence, less stable maladjustment. It had the ability of dealing with many signals, including noncorrelation signal and strong correlation signal. However, its computational complexity was comparable to that of NLMS algorithm. Simulation results show that for noncorrelation signal, the stable maladjustment of the proposed algorithm is less than that of VS-NLMS algorithm, and its convergence is comparable to that of the algorithm proposed in reference but faster than that of L.E-LMS algorithm. For high correlation signal, its performance is superior to those of NLMS algorithm and DCR-LMS algorithm.